Mold preparation for stir casting of aluminium matrix composite brake motor: a review - Adetayo A., Adebisi (UM, 2010)
The production of composite material parts for automotive applications has grown steadily in recent years and is projected to show further growth in the nearest future. This composite automotive part undergoes casting or foundry processes such as mold preparation which is an essential component in the foundry industry. In this paper, the effects of the oil-tempered sand in the preparation of sand mold was studied and compared with permanent mold for stir casting of aluminium matrix composite (AMC) brake rotor. The production parameters such as casting complex shapes, cost, surface finish, and mechanical properties were considered for the preparation of the molds while the relatively lower cost stir casting technique were evaluated for the development of SiCp reinforced AMC brake rotor. The study showed that the oil tempered sand mold could produce surface quality close be a better choice for the production of brake rotor in terms of surface quality which is close to metal or permanent mold with flexible casting shapes and lower cost.